IMPLEMENTATION AND DEVELOPMENT OF MODERN METHODS OF PRACTICE-ORIENTED TRAINING (DUAL TRAINING) (Ustozlar uchun, 2026)
The article reveals some problems of the higher professional education system of the Republic of Uzbekistan in the context of improving the quality of training specialists. The emphasis is placed on the professional development of a student – a future teacher and involves mastering the experience of professional activity within a certain orientation (profile). The methodological basis for solving the problem of the professional development of students - future teachers is an appeal to the practice-oriented approach in the process of their preparation. The implementation of this approach can represent the introduction of practice-oriented learning technologies and the introduction of the dual educational system.